On Vietoris Soft Topology I - Shakir, Q. R. (Journal of Scientific Research, 2016)
In this article, we define the hyperspace of soft closed sets of a soft topological space (FA, ?). In addition, we define the Vietoris soft topology, ?v, by determining the soft base of this topology which has the form ?FH1, FH2,.....FHn?, where ?FH1, FH2,.....FHn? are soft open sets in (FA, ?). Some properties of this topology are also investigated. The impact of introducing the Vietoris soft topology is to enable us to understand many properties of the structure of soft topologies corresponding to it.